Governance and Economic Growth Nexus: Challenges and Opportunities for Pakistan; Post Covid-19 Analysis - Subhan, Qazi Abdul; Abdullah; Iqbal, Tabassum (iRASD Journal of Economics, 2023)
Post novel coronavirus-19 has created a challenging situation for developed as well as developing countries to sustain their economic stability. There are lot of controversies for policy makers to formulate an effective governance policy for reviving economic strength and to minimize economic effects of this pandemic. The present study focuses on the deliberation of current state of economy in Pakistan after 4th wave of COVID-19. This study further analyzes the effects of governance policies for restoring economic stability in Pakistan. To measure governance, world governance indices (WGI) has been used while economic stability has been measured through growth in GDP per capita. The data about economic and social indicators has been collected for the period of 1996 to 2021. To ascertain the empirical results, multiple linear regression model has been applied. Main results are in favor of positive and significant effects of governance effectiveness on economic stability of the country. Future studies may focus on the role of effective governance policies to achieve economic stability in regional blocks like EU, ASEAN, G 20 and OECD.